Hierarchical bank supervision - Rafael Repullo (SERIEs - Journal of the Spanish Economic Association, 2018)
This paper presents a model in which a central and a local supervisor contribute their efforts to obtain information on the solvency of a local bank, which is then used by the central supervisor to decide on its early liquidation. This hierarchical model is contrasted with the alternatives of decentralized and centralized supervision, where only the local or the central supervisor collects information and decides on liquidation. The local supervisor has a higher bias against liquidation (supervisory capture) and a lower cost of getting local information (proximity). Hierarchical supervision is the optimal institutional design when the bias of the local supervisor is high but not too high and the costs of getting local information from the center are low but not too low. With low (high) bias and high (low) cost it is better to concentrate all responsibilities in the local (central) supervisor.
Keywords: G21; G23; D02; 330; Centralized versus decentralized supervision; Strategic information acquisition; Bank solvency; Bank liquidation; Supervisory capture; Optimal institutional design